HBR's 10 must reads on talent - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2022)
"Top talent is hard to come by. And seeing them walk out the door can be painful-and expensive. You need to take proactive steps to ensure that you attract, develop, and retain your best people. If you read nothing else on managing talent in your organization, read these 10 articles. We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you ensure that your star employees stay engaged, grow their skills, and remain committed to your organization. This book will inspire you to: build a talent strategy for your organization; reinvent HR and bring on a CHRO; identify and develop high-potential employees; reengineer your recruitment processes to attract stellar candidates; create a learning culture within your organization; and use people analytics to study influence and innovation"--
Building a Game-Changing Talent Strategy / by Douglas A. Ready, Linda A. Hill, and Robert J. Thomas -- Your Approach to Hiring Is All Wrong / by Peter Cappelli -- "A Players" or "A Positions"? : The Strategic Logic of Workforce Management / by Mark A. Huselid, Richard W. Beatty, and Brian E. Becker -- Turning Potential into Success : The Missing Link in Leadership Development / by Claudio Fernández-Aráoz, Andrew Roscoe, and Kentaro Aramaki -- Making Business Personal / by Robert Kegan, Lisa Lahey, Andy Fleming, and Matthew Miller -- The Power of Hidden Teams / by Marcus Buckingham and Ashley Goodall -- The Performance Management Revolution / by Peter Cappelli and Anna Tavis -- People Before Strategy : A New Role for the CHRO / by Ram Charan, Dominic Barton, and Dennis Carey -- Toward a Racially Just Workplace / by Lauren Morgan Roberts and Anthony J. Mayo -- How to Do Hybrid Right / by Lynda Gratton -- Your Workforce Is More Adaptable Than You Think / by Joseph Fuller, Judith K. Wallenstein, Manjari Raman, and Alice de Chalendar.
Includes index.
Description based on online resource; title from digital title page (viewed on January 06, 2023).
WorldCat record variable field(s) change: 050
Keywords: Personnel management; Success in business; Ability; Ability; Personnel management; Success in business; elektronické knihy; electronic books